SISTEM INFORMASI MANAJEMEN PERTANAHAN NASIONAL PADA KANTOR PERTANAHAN KOTA TERNATE PROVINSI MALUKU UTARA - GALANGBULAENG, VERAWATI OLIVIA; Rumapea, Patar; Rares, joyce Jacinta (JURNAL ADMINISTRASI PUBLIK, 2016)
In general, when people talk or hear the term Management Information System (MIS), then reflected in their minds is a system that was created to carry out-processing the data into information to be used by an organization or certain parties who need information about. Based on the identification of the problem, it can be formulated problems in this study, namely: "how the management of national land management information system (SIMTANAS) in support of the effective implementation of the tasks of land in the city of Ternate Land Office". This study aimed to describe the management of national land management information system (SIMTANAS) in support of the effective implementation of the tasks of land at the Land Office of Ternate.Referring to the results of research, as has been noted in the previous section, it can be drawn some conclusions, as follows: The results showed that the implementation of the eight principles SIMTANAS at the offices of the Land of Ternate, in general has been running well, but has not been optimal so that some criteria / indicators that have not achieved the relevance, timeliness and consistency. The effectiveness of the implementation of the tasks of land, especially in the Land Office of Ternate, in general has been running as expected, although not yet reached the optimal result that some of the criteria effectiveness of the implementation of the tasks of the land has not been achieved, namely the ability of initiative, creativity and responsibility, satisfaction work, the quality and quantity of work. SIMTANAS support the effectiveness of the implementation of the tasks of land, especially in the Land Office Ternate pretty good, although not yet fully achieved. Not optimal SIMTANAS dikungan on the effectiveness of the implementation of the tasks indicated by the weak land some SIMTANAS performance indicators, such as relevansi, timely and consistency. Based on some of the results of all this research, it can put forward some suggestions as follows: In order to optimize the implementation of the principle of SIMTANAS at the Land Office of Ternate, it is necessary to spur the implementation of some of the principles that have not been achieved, the principle of relevance, timeliness and consistency. To optimize the effectiveness of the implementation of the tasks of land, it is necessary to accelerate the ability of initiative, creativity and responsibility, job satisfaction, quality and quantity of the work of employees, especially at the Land Office of Ternate. To increase the carrying capacity SIMTANAS on the effectiveness of the implementation of the tasks of land at the Land Office of Ternate, need to work on improving the performance of some of the principles SIMTANAS, such as relevance, timeliness and consistency by improving the system equipment and job skills training, both for power electronic engineering and power fieldworkers.Keywords: National Land Systems